Two appeals admissible and three inadmissible. Commentary on the judgement of the European Court of Human Rights in the case Inmobilizados y Gestiones S. L. v. Spain, 14 September 2021 (Revista de Estudios Europeos, 2022)
.
Keywords: European Court of Human Rights; Human Rights